2019 Physics Education Research Conference Proceedings 2020
DOI: 10.1119/perc.2019.pr.kalender
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the role of prior preparation and self-efficacy on female and male students’ introductory physics course achievements

Abstract: Research suggests that self-efficacy is one of the central factors predicting students' engagement, participation and retention in STEM fields. Physics is one of the STEM fields in which women are severely underrepresented. Prior research has found that there is a gender gap in conceptual assessments and sometimes even in the final exam favoring men. Women also report lower self-efficacy than men in physics. The origins of these gender disparities are complex, not well understood, and include systemic societal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…In modelling both the FCI post-test and exam, self-efficacy emerged as a significant predictor. The importance of selfefficacy is consistent with several recent studies [15,16,18]. In Ref.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In modelling both the FCI post-test and exam, self-efficacy emerged as a significant predictor. The importance of selfefficacy is consistent with several recent studies [15,16,18]. In Ref.…”
Section: Discussionsupporting
confidence: 92%
“…In this report, we focus on gender disparities in self-efficacy and test anxiety. Self-efficacy influences the choices someone makes and the effort they put forth in a task [14], and it's been shown to be related to performance in physics in [13,15,16] and to physics identity [17]. Ballen et al [18] showed that selfefficacy mediated learning gains for underrepresented minority students in a biology course, identifying self-efficacy as a possible avenue for supporting equity-seeking groups.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, one mechanism by which this occurs is the feedback loop between course grades and self-efficacy [89][90][91][100][101][102][103]. Other studies at this same university have found significant gender differences favoring men in the physics self-efficacy of students in large introductory physics courses [41,42,55,56,65,67,68], consistent with studies at other universities [104,105]. Although our analysis only includes students who had not only declared a physics major but had also completed the modern physics course in the sophomore year, the gender differences in grades earned in introductory physics courses could have a large, gender differential impact on students' choice to pursue physics and related majors, despite the fact that performance in introductory physics does not predict performance in advanced physics courses.…”
Section: Discussionmentioning
confidence: 96%
“…There has been much important work done in recent years studying the many and various ways that women are not being adequately supported by their physics departments [8,21,. In particular, inequitable gender differences in introductory physics classes have been documented with a variety of measures including motivational characteristics [40-42, 54-56, 59, 60, 62, 65-74], grades [20,46,47,56,61,[65][66][67][68]73], and performance on conceptual inventories [8,24,25,50,51,57,58]. The overarching theme of these studies' conclusions is in line with broader studies of gender inequity in physics and STEM [26, 34-36, 43-45, 48, 49, 53, 64] which highlight the significant obstacles faced by women in STEM which arise from societal stereotypes and biases.…”
Section: Introductionmentioning
confidence: 99%
“…Additional contributions to the lack of women and students of color in physics come from dissimilar pre-college experiences. Previous research has shown that students' success in introductory physics courses can be predicted by certain factors during their high school experiences [10][11]; however, research also indicates that these experiences are not the same for women and students of color as they are for white men and may negatively impact their success in and selection of a physics major post high school [12][13][14].…”
Section: Introductionmentioning
confidence: 99%